Addressing knowledge and behavior gaps in breast cancer risks: implications for health promotion and intervention strategies - Effiong, Magdalene Eno; Afolabi, Israel Sunmola; Chinedu, Shalom Nwodo (Frontiers in Oncology, 2024)
IntroductionThe growing incidence and high mortality rate of breast cancer (BC) in Nigeria is attributed to increased risk levels, poor prognosis and late detection.MethodsThis study aimed at identifying education-based disparities in BC risk knowledge, lifestyle/ dietary patterns among females in Ogun state, Nigeria. Questionnaires were used to obtain data from 1135 study participants across various levels of education and analyzed using Epi-info software and Graphpad prism.ResultsThe lifestyle/dietary pattern assessment revealed that the participants in the secondary level smoked the most (4.50%), accompanied by high red wine (31.00%), fruits and vegetable (73.00%) consumption. Graduates had the highest antibiotics intake (54.50%) and alcohol consumption (12.00%), the undergraduates were the most physically inactive (63.90%) with the highest consumption of carbonated drinks (73.90%), postgraduates consumed red meat/smoked foods the most (70.70%).DiscussionThe knowledge of BC risk positively impacted carbonated drinks, physical inactivity, smoking, antibiotics and alcohol intake. However, it did not affect family history, red meat/smoked foods, fruits and vegetables consumption. Overall, Education has an impact on the knowledge of BC risks which influences the lifestyle/dietary patterns of females in Nigeria.